Empowering Students Through Discovery Learning Approach - Milahtul Latifah (al-Afkar, Journal For Islamic Studies, 2023)
Abstract: The learning model must be adjusted to the level and characteristics of the class, the subject matter to be discussed, the availability of learning media, and others. So it is very important to determine the right learning model to be used in a lesson so that the goals or learning outcomes are achieved. The Discovery Learning strategy is a component of a constructivist approach that has a long history in education. The idea of ​​discovery learning arises from the desire to give pleasure to children/students in "discovering" something by themselves, by following in the footsteps of scientists. Implementation in cycles I-III of the Discovery Learning learning model The allocation of learning time is more effectively and efficiently arranged so that if there are obstacles in the process of teaching and learning activities they can be resolved immediately properly, this can be seen from the 10 students who complete 10 people with a percentage of 100%. Students who did not complete amounted to 0 with a percentage of 0%. With an average score of 82 classical student completeness is 100% with a KKM (Minimum Completeness Criteria) score of 75. These results show that the discovery learning approach has a good impact on empowerment in terms of cognitive, psychomotor, and student affection towards significant changes in students in terms of understanding and self-confidence, of course.